THE EFFECT OF DISTANCE LEARNING THROUGH LEARNER CENTER MICROTEACHING MODEL ON PCK, EXPERIENCE, PERFORMANCE, AND PROFESSIONAL AWARENESS - Adrianus Nasar; Melkyanus Bili Umbu Kaleka; Helena Vidamsi Alung (OPTIKA: Jurnal Pendidikan Fisika, 2020)
This study aims to see the effect of distance learning through LCMT, experience, performance, and professional awareness of 6th semester students of the Physics Education study program. This study used an experimental method with a posttest design with 33 respondents. Data collection was carried out using a questionnaire technique with 33 items of instruments. Data for each instrument item using a Likert scale with the accumulated number of each instrument item. The results showed that the effect of distance learning through LCMT had a very high effect on PCK (score 149), experience (score 142), performance (score 146), and on professional awareness (score 144).